The Effect Of Work-Life Balance And Performance Management On Employee Performance At The Population Control, Family Planning, Women's Empowerment And Child Protection (Dp2kbp3a) Office Of Buleleng Regency - Putu Gilang Mas Suputra; Ni Made Ary Widiastini; Made Ary Meitriana (STEBIS Bina Mandiri, 2026)
This study aims to analyze the influence of Work-Life Balance on Employee Performance, the effect of Performance Management on Employee Performance, the effect of Work-Life Balance on Performance Management, and the mediating role of Performance Management in the relationship between Work-Life Balance and Employee Performance at the Population Control, Family Planning, Women's Empowerment, and Child Protection (DP2KBP3A) Office of Buleleng Regency. This study uses a mixed-methods approach with a Sequential Explanatory design. The research population consisted of 85 employees of DP2KBP3A Buleleng Regency, and the entire population was sampled using a total sampling technique. Quantitative data were collected using questionnaires, while qualitative data were obtained through in-depth interviews. Quantitative data analysis using multiple linear regression with the help of SPSS. The results showed that Work-Life Balance had a positive and significant effect on Employee Performance (β = 0.540; Sig. = 0.000), Performance Management had a positive and significant effect on Employee Performance (β = 0.365; Sig. = 0.001), and Work-Life Balance had a positive and significant effect on Performance Management (β = 0.873; Sig. = 0.000). Simultaneously, Work-Life Balance and Performance Management had a significant effect on Employee Performance (F = 136.881; Sig. = 0.000) with a determination coefficient value of 77.0% (R² = 0.770). The results of the path analysis showed that Performance Management played a mediating role, with an indirect effect of 0.318. This study concludes that improving work-life balance and strengthening performance management systems are strategic factors in improving employee performance in public sector organizations.